2002
DOI: 10.1523/jneurosci.22-17-07485.2002
|View full text |Cite
|
Sign up to set email alerts
|

cGMP/Protein Kinase G-Dependent Inhibition of N-Type Ca2+Channels Induced by Nitric Oxide in Human Neuroblastoma IMR32 Cells

Abstract: Although data from our laboratory and others suggest that nitric oxide (NO) exerts an overall inhibitory action on high-voltageactivated Ca 2ϩ channels, conflicting observations have been reported regarding its effects on N-type channels. We performed whole-cell and cell-attached patch-clamp recordings in IMR32 cells to clarify the functional role of NO in the modulation of N channels of human neuronal cells. During depolarizing steps to ϩ10 mV from V h ϭ Ϫ90 mV, the NO donor, sodium nitroprusside (SNP; 200 M)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 59 publications
4
29
0
Order By: Relevance
“…According to current literature, the role of PKG in TH activity regulation is rather controversial. It was reported that NO induces cGMP/PKG-dependent inhibition of N-type Ca 2ϩ channels in neuroblastoma cells (8). Furthermore, the NO/cGMP/PKG pathway is associated with reduced calcium entry to the cell (7,26).…”
Section: Discussionmentioning
confidence: 98%
“…According to current literature, the role of PKG in TH activity regulation is rather controversial. It was reported that NO induces cGMP/PKG-dependent inhibition of N-type Ca 2ϩ channels in neuroblastoma cells (8). Furthermore, the NO/cGMP/PKG pathway is associated with reduced calcium entry to the cell (7,26).…”
Section: Discussionmentioning
confidence: 98%
“…NO reduces the intracellular Ca 2+ concentration in SMC by inhibiting sarcoplasmic reticulum (SR). Ca 2+ release through both IP3R and RyR [5] , and Ca 2+ influx through N-channel gating via cGMP and PKG [14] . cGMP can modulate Ca 2+ spark activity by decreasing myofibrillar Ca 2+ sensitivity and increasing Ca 2+ uptake by the SR [6] .…”
Section: Discussionmentioning
confidence: 99%
“…In the vestibular system of the chinchilla and rat, NADPH-d histochemistry and NOS-I positive immunoreactivity were found in a subpopulation of vestibular-efferent neurons contacting hair cells (Lysakowski and Singer 2000). NOS-I, calretinin, and sGC were co-localized in calyx-ending afferent neurons of the chinchilla and both sGC and calmodulin, an important cofactor of NOS (Bredt 1999), were co-localized in type I and type II hair cells (Desai et al 2004;Dhaliwal and Lysakowski 2000). NOS was colocalized with sGC and cGMP in the sensory epithelia and the vestibular nerve fibers of the guinea pig and mice (Hess et al 1998a,b).…”
Section: Introductionmentioning
confidence: 99%